(untitled) (Revista INTEREDU11, 2021)
Notwithstanding the teacher training education has evolved towards an early insertion into real-work spaces to allow the link between the development of higher-order thinking skills and the complexities of real educational contexts, the change in the teaching-learning dynamics is still slow and so require a makeover to allow them to take advantage of current under-degree students and their different learning contexts. The objective of this study was to assess the implementation of effective teaching-learning strategies in an under-degree programme for early-education students who were encouraged to use a new set of lesson design during their practicum hours, as an effective articulator axe between theory and practice, in real learning contexts. This intervention was assessed under a qualitative, exploratory approach, through the case studies of seven students and one teacher. Personal interviews were conducted and by using a comparison method, and their new class materials were revised, too. Results reveal a high level of relevance, sequencing of the activities, an increase in motivation as the programme unfolded, and a positive result from this simulation as an effective approach to the educational reality. On the other hand, there are still some difficulties to develop a dialogic perspective of action-reflection dynamic for the resolution of pedagogical issues, and so, to be able to move forward to a deeper comprehension of real educational contexts.